The Importance of Access to the SCOPUS Database in the Economic Crisis Condition - Atefeh Kalantari; Hassan Jahanihashemi; Masumeh Karbala Aghaei Kamran (International Journal of Information Science and Management, 2014)
Data acquisition and delivering information resources to clients are among the most vital functions of libraries. However, current political and economic crisis has imposed unpleasant effects on these functions. In such conditions, selecting information resources becomes an ever more complex task. This research intends to answer the question on whether or not the purchase of Scopus services in such a crisis, which makes the subscription of credible scientific journals much more difficult, is a beneficial choice for Iranian medical libraries. The problem will be answered by analyzing the accessibility to full text articles via “view at publisher” image links in Scopus database. Different studies have already been carried out on the abilities and features of Scopus database in scientometric and citation analysis. However, it seems that current study is the first research to examine the value and importance of existing link for accessing the full-text articles such as "view at publisher" link. This link is one of the remarkable features devised in Scopus which has a special importance for end users. Hence, access ratio to full-text documents cited in articles written by Iranian medical faculties was studied through the "view at publisher" link in Scopus, and also via a link devised in the A-Z list of full-text journals in the Iranian National Medical Digital Library database, available at URL: www.inlm.org, followed by comparing the results obtained through the study. Results showed the ability of Scopus to make full-text articles accessible for users' depending on the type and level of individuals or institutional subscription. Such ability itself could justify the necessity for subscribing to Scopus by the universities of medical sciences. Regardless of other features of Scopus such as scientometric studies, etc., this ability becomes more important when access to some articles depends on paying subscription fee either privately or institutionally. Moreover, this ability provides the end-users to have access to a large volume of free papers. So, Scopus could be introduced as a gateway/portal for an easier access to full-text documents of various databases.